Hydrophilic carbon-based material modified high-entropy alloy water electrolysis hydrogen production catalyst as well as preparation method and application thereof
By using hydrophilic carbon-based materials to modify the electrolytic hydrogen production catalyst of high-entropy alloy, the problem of hydrogen bubble accumulation during the electrolysis process is solved, and more efficient hydrogen generation and more stable catalyst performance are achieved.
Patent Information
- Application Number
- CN202411762703.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
There are many hydrogen bubbles on the surface of existing electrolytic water hydrogen production catalysts, which leads to the need to remove the influence of hydrogen bubbles through stirring during the electrolytic water process. This method is not practical in large-scale industrial production.
The hydrophilic carbon-based material modified high-entropy alloy water-generated hydrogen production catalyst is used to obtain a hydrophilic carbon-based material-modified high-entropy alloy water-generated hydrogen production catalyst by ultrasonic mixing the hydrophilic carbon-based material and mixed metal salt in an ethylene glycol solution, and then heat treatment under oil bath conditions.
By modifying the hydrophilicity of the catalyst, the accumulation of hydrogen bubbles on the catalyst surface is reduced, the hydrogen generation efficiency is improved, energy consumption is reduced, and the stability of the catalyst is improved.
Smart Images

Figure CN119524874A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and relates to a method and application of modifying a high entropy alloy water electrolysis catalyst by using a hydrophilic carbon-based material, and specifically relates to a hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst, and a preparation method and application thereof. Background Art
[0002] The ever-increasing global energy demand, coupled with the gradual depletion of fossil fuels and environmental degradation, has prompted people to urgently seek renewable energy sources such as wind and solar energy. However, there is usually a time gap between the supply and demand of these sustainable energy sources. Water electrolysis is a promising clean and sustainable energy technology for hydrogen production. Hydrogen has high calorific value, clean combustion products and renewable characteristics, making it one of the most ideal energy carriers. Finding a green and efficient method for hydrogen production is the main challenge facing the large-scale utilization of hydrogen energy. Electrochemical water splitting technology can not only convert electrical energy into chemical energy in an environmentally friendly way, but also can be easily combined with other intermittent energy sources (such as wind and solar energy), providing a promising solution for the production of high-purity hydrogen.
[0003] High entropy alloy catalysts have the advantages of high efficiency, stability, and reusability, and are perfectly suitable for the reaction of hydrogen production by water electrolysis. However, when designing efficient catalysts, in addition to considering the catalytic material, the formation and release of hydrogen bubbles on the catalyst surface should also be considered, because this will significantly affect the catalytic performance. Hydrogen bubbles adhering to the catalyst surface reduce the effective specific surface area, increase the activation overpotential, and block the transport of ions through the electrolyte, resulting in an increase in the overpotential of the catalyst. In addition, the evolution of hydrogen bubbles will produce a large tensile force, and when the hydrogen bubbles detach, they will destroy the catalyst, thereby reducing the stability of the catalyst. In the water electrolysis experiment, it is indeed a common method to apply external force by stirring the electrolyte to promote the hydrogen bubbles generated during the electrolysis process to detach faster from the electrode surface. This method can effectively reduce the impact of bubbles on the electrolysis reaction and improve the electrolysis efficiency. However, the method of stirring the electrolyte to apply external force is not practical in large-scale industrial production, because continuous stirring increases energy consumption and may lead to equipment complexity. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst and its preparation method and application, so as to solve the technical problem that there are many hydrogen bubbles on the surface of the existing water electrolysis hydrogen production catalyst, and the influence of hydrogen bubbles must be eliminated by stirring during the water electrolysis process.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a hydrogen production catalyst by electrolyzing water using a hydrophilic carbon-based material-modified high entropy alloy, comprising: The hydrophilic carbon-based material and the mixed metal salt are added to an ethylene glycol solution, and ultrasonically mixed to obtain a reaction solution. The reaction solution is heat-treated for 0.5-2 h in an oil bath at 200-240° C., and centrifuged after cooling to obtain a hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst.
[0006] Preferably, the steps include: 1) adding the hydrophilic carbon-based material and the mixed metal salt into the ethylene glycol solution, and uniformly mixing them by ultrasonication to obtain a reaction solution; 2) The ethylene glycol solution is heated to 200-240° C. in an oil bath, and then the reaction solution prepared in step 1) is slowly added thereto, and the mixture is heated for 0.5-2 h. After cooling, the mixture is centrifuged to prepare a carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst.
[0007] Preferably, the hydrophilic carbon-based material is selected from hydrophilic carbon black, hydrophilic carbon cloth or hydrophilic biochar material.
[0008] Preferably, the purity of the ethylene glycol solution is 99.7% (Gas Chromatography, GC)).
[0009] Preferably, the mixed metal salt is prepared from platinum salt, palladium salt, cobalt salt, nickel salt and copper salt.
[0010] More preferably, the mixed metal salt is acetylacetonate metal salt.
[0011] More preferably, the mixed metal salt is prepared from platinum acetylacetonate, palladium acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate and copper acetylacetonate of the same molar mass.
[0012] Preferably, in step 1), the usage ratio of the carbon-based material and the mixed metal salt is (0.3-0.4) mg: (0.1-0.2) mmol.
[0013] Preferably, in step 1), the ultrasonic mixing time is 0.25-0.75 h.
[0014] Preferably, in step 2), the reaction solution is 230-260 μLs -1 The reaction is more complete and the size distribution of the product particles is more uniform.
[0015] The invention also discloses a carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst prepared by the above method, and the carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst has enhanced hydrophilicity.
[0016] The present invention also discloses the application of the carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst in water electrolysis hydrogen production reaction.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for modifying a mixed metal salt high entropy alloy water electrolysis hydrogen production catalyst using a hydrophilic carbon-based material. On the one hand, in order to optimize the performance of the catalyst and enhance the hydrophilicity of the catalyst, the present invention selects a hydrophilic carbon-based material to enhance the hydrophilicity of the catalyst. By adding a hydrophilic carbon-based material, the surface properties of the catalyst can be effectively improved, so that the generated hydrogen bubbles are more easily separated, thereby reducing the gas accumulation phenomenon and improving the reaction efficiency; on the other hand, before the reaction, the reaction solution containing the mixed metal salt is mixed evenly and slowly added dropwise to the reaction solvent. This operation can ensure that the raw material particle size and element distribution are uniform during the preparation of the catalyst, which helps to improve the efficiency and selectivity of the catalytic reaction. This uniform structure can provide more catalytic sites, promote the adsorption and conversion of reactants, and thus enhance the performance of water electrolysis hydrogen production. In addition, the uniform element distribution helps to optimize the electronic and ionic conductivity of the catalyst, further enhancing the overall catalytic effect. Therefore, the present invention combines the above two invention points to form an innovative solution, which can not only maintain the activity of the catalyst, but also improve its surface hydrophilicity, thereby achieving a more efficient electrocatalytic reaction. This optimization method provides new ideas for the design and application of electrocatalysts, which will help promote the development of renewable energy technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a flow chart for preparing the high entropy alloy catalyst of the present invention; Figure 2 X-ray diffraction images of high entropy alloy catalysts prepared in three embodiments of the present invention; Figure 3 is a scanned image of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1; Figure 4 This is a scanned image of the PtPdCoNiCu-Graphene high entropy alloy catalyst prepared in Example 2; Figure 5 This is a scanned image of the PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3; Figure 6 This is a contact angle image of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1; Figure 7 This is a contact angle image of the PtPdCoNiCu-Graphene high entropy alloy catalyst prepared in Example 2; Figure 8 This is a contact angle image of the PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3; Fig. 9 The hydrogen evolution reaction polarization curves of the high entropy alloy catalysts prepared in the three embodiments of the present invention corresponding to the linear sweep voltammetry method; Fig.10 The local fitting curves are the polarization curves of hydrogen evolution reaction obtained by linear sweep voltammetry corresponding to the high entropy alloy catalysts prepared in the three embodiments of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0020] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings: The process flow of the high entropy alloy water electrolysis hydrogen production catalyst in all embodiments of the present invention is as follows Figure 1 As shown, it is synthesized by a simple one-step solvothermal method, which includes the following steps: 1) Prepare a mixed solution of metal salts, and add or not add carbon-based materials as required as a reaction solution; 2) Add the reaction solution to perform heat treatment under oil bath conditions, and obtain a high entropy alloy water electrolysis hydrogen production catalyst after cooling and centrifugation.
[0022] Example 1 No addition of carbon-based materials A method for preparing a PtPdCoNiCu high entropy alloy catalyst comprises the following steps: 1) Weigh the same molar mass of platinum acetylacetonate (Pt), palladium acetylacetonate (Pd), cobalt acetylacetonate (Co), nickel acetylacetonate (Ni) and copper acetylacetonate (Cu). The total mass of the mixed metal salts weighed is 38.0 mg. Add the weighed drugs into 5 mL of ethylene glycol solution and ultrasonically mix them evenly.
[0023] The specific preparation process is as follows: 0.025 mmol of metal salts were weighed on a balance, placed in a beaker containing 5 mL of ethylene glycol solution, and ultrasonicated for 0.5 h.
[0024] 2) Add 5 mL of ethylene glycol solution into the flask and heat to 220 °C in an oil bath.
[0025] The specific preparation process is as follows: 5 mL of ethylene glycol and a magnet are added into a flask. During the oil bath heating process, the magnet must also be rotated to ensure that the solution is heated evenly.
[0026] 3) The ultrasonically homogenized reaction solution was slowly dripped into the flask and reacted at 220 °C to obtain a PtPdCoNiCu high entropy alloy electrocatalyst.
[0027] The specific preparation process is as follows: the reaction solution is pipetted at 230 ~ 260 μLs -1 Slowly add it dropwise into the flask.
[0028] Example 2 Adding hydrophobic carbon-based materials A method for preparing a PtPdCoNiCu-Graphene high entropy alloy catalyst comprises the following steps: 1) Weigh it on a balance and add it to the ethylene glycol solution and mix well.
[0029] Specifically, first weigh 0.025 mmol of platinum acetylacetonate (Pt), 0.025 mmol of palladium acetylacetonate (Pd), 0.025 mmol of cobalt acetylacetonate (Co), 0.025 mmol of nickel acetylacetonate (Ni), 0.025 mmol of copper acetylacetonate (Cu), and 0.4 mg of hydrophobic graphene powder (0.4 mg is theoretically 4% of the mass of the high entropy alloy generated by the complete reaction of 0.025 mmol of the metal salt solution). Then add 5 mL of ethylene glycol solution to the weighed drugs, and ultrasonicate them for 0.5 h to obtain a reaction solution.
[0030] 2) Add 5 mL of ethylene glycol solution into the flask and heat to 220 °C in an oil bath.
[0031] The specific preparation process is as follows: 5 mL of ethylene glycol and a magnet are added into a flask. During the oil bath heating process, the magnet must also be rotated to ensure that the solution is heated evenly.
[0032] 3) The ultrasonically homogenized reaction solution was slowly dripped into the flask and reacted at 220 °C to obtain a PtPdCoNiCu-Graphene high entropy alloy catalyst.
[0033] The specific preparation process is as follows: the reaction solution (ethylene glycol solution containing metal salt) homogenized by ultrasonic in step 1) is heated to 230 ~ 260 μLs -1 The mixture was slowly added dropwise into a flask at 220 °C at a rate of 1.000 ℃. The mixture was heated at 220 °C for 1 h. After cooling, the PtPdCoNiCu-Graphene high entropy alloy catalyst powder was obtained by centrifugation.
[0034] Example 3 Adding hydrophilic carbon-based materials A method for preparing a PtPdCoNiCu-CB high entropy alloy catalyst comprises the following steps: 1) Weigh it on a balance and add it to the ethylene glycol solution and mix well.
[0035] Specifically, first weigh 0.025 mmol of platinum acetylacetonate (Pt), 0.025 mmol of palladium acetylacetonate (Pd), 0.025 mmol of cobalt acetylacetonate (Co), 0.025 mmol of nickel acetylacetonate (Ni), 0.025 mmol of copper acetylacetonate (Cu), and 0.4 mg of hydrophilic carbon black powder (0.4 mg is theoretically 4% of the mass of the high entropy alloy generated by the complete reaction of 0.025 mmol of the metal salt solution). Then add 5 mL of ethylene glycol solution to the weighed drugs, and ultrasonicate them for 0.5 h to obtain a reaction solution.
[0036] 2) Add 5 mL of ethylene glycol solution into the flask and heat to 220 °C in an oil bath.
[0037] The specific preparation process is as follows: 5 mL of ethylene glycol and a magnet are added into a flask. During the oil bath heating process, the magnet must also be rotated to ensure that the solution is heated evenly.
[0038] 3) Slowly drop the ultrasonically homogenized reaction solution into the flask and react at 220°C to obtain a PtPdCoNiCu-CB high entropy alloy catalyst.
[0039] The specific preparation process is as follows: the previously ultrasonically homogenized reaction solution (ethylene glycol solution containing metal salt) is heated at 230 ~ 260 μLs -1 The mixture was slowly added dropwise into a flask at 220 °C at a rate of 1.000 ℃. The mixture was heated at 220 °C for 1 h. After cooling, the PtPdCoNiCu-CB high entropy alloy catalyst powder was obtained by centrifugation.
[0040] The PtPdCoNiCu high entropy alloy electrocatalyst prepared in Example 1, the PtPdCoNiCu-Graphene high entropy alloy catalyst prepared in Example 2, and the PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3 were subjected to corresponding catalyst structure and performance tests, and the results were as follows: Figure 2-Figure 10 The specific analysis is as follows: See also Figure 2 , are X-ray diffraction (XRD) images of the three high entropy alloy catalysts prepared. It can be seen from the figure that the PtPdCoNiCu-Graphene high entropy alloy catalyst synthesized in Example 2 mainly has three peaks in the range of 20 ~ 80°. These three peaks are at 42°, 47° and 71° respectively. The positions of these peaks are also different from the peaks of Pt, Pd, Co, Ni and Cu single atoms, but are the same as the peaks of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1, and are located in the middle of the (1 1 1), (2 0 0) and (2 2 0) crystal planes of Pt, Pd, Co, Ni and Cu single atoms, respectively. This shows that the peaks formed by the PtPdCoNiCu-Graphene high entropy alloy catalyst are the peaks formed by their alloys, and are (1 1 1), (2 0 0) and (2 2 0) crystal planes respectively.
[0041] at the same time, Figure 2 The PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3 has three main peaks in the range of 20 ~ 80°. These three peaks are at 42°, 47° and 71° respectively. The positions of these peaks are the same as those of Pt, Pd, Co, Ni, and the peaks of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1, and are respectively located in the middle of the (1 11), (2 0 0) and (2 2 0) crystal planes of Pt, Pd, Co, Ni and Cu single atoms, which indicates that the peaks formed by the PtPdCoNiCu-CB high entropy alloy catalyst are the peaks formed by their alloys, and are respectively (1 1 1), (2 0 0) and (2 2 0) crystal planes.
[0042] See also Figure 3, is a scanning field emission electron microscope (SEM) image of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1. It can be seen from the figure that the PtPdCoNiCu high entropy alloy catalyst is particles of relatively uniform size.
[0043] See also Figure 4 , is a scanning field emission electron microscope (SEM) image of the PtPdCoNiCu-Graphene catalyst prepared in Example 2. It can be seen from the figure that the PtPdCoNiCu-Graphene catalyst is particles of relatively uniform size.
[0044] See also Figure 5 , is a scanning field emission electron microscope (SEM) image of the PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3. From the image, it can be seen that the PtPdCoNiCu-CB high entropy alloy catalyst is particles of relatively uniform size.
[0045] See also Figure 6 , which is a contact angle image of the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1. As can be seen from the figure, its contact angle is 65.1°.
[0046] See also Figure 7 , which is a contact angle image of the PtPdCoNiCu-Graphene high entropy alloy catalyst prepared in Example 2. As can be seen from the figure, its contact angle is 71.4°, and its hydrophilicity is weakened relative to the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1.
[0047] See also Figure 8 , which is a contact angle image of the PtPdCoNiCu-CB high entropy alloy catalyst prepared in Example 3. It can be seen from the figure that the contact angle of the PtPdCoNiCu-CB high entropy alloy catalyst is 58.3°, and its hydrophilicity is enhanced compared with the PtPdCoNiCu high entropy alloy catalyst prepared in Example 1.
[0048] See also Fig. 9 and Fig.10 , respectively, the high entropy alloy catalysts prepared in the three embodiments are the voltammetric linear sweep method alkaline HER polarization curves and the fitting results of their volatility. Fig. 9 It can be seen that the performance of the catalyst after adding acetylene black is slightly reduced under high current conditions (j>0.75 A cm -2 ), and the stability of the catalyst is weakened. Fig.10 It can be seen that after adding acetylene black, the catalyst -2 ), the performance of the catalyst was improved, and its volatility under high current conditions was reduced. Further, through the analysis of the relevant performance activities of the two carbon-based material modified high entropy alloy catalysts prepared in Example 2 and Example 3, it can be seen that: adding hydrophobic graphene to the reaction solution of the synthetic catalyst to increase the active area of the catalyst can theoretically improve the performance of the electrocatalyst. However, the experimental results show that the addition of hydrophobic materials will cause the hydrophilicity of the catalyst to weaken, making it difficult for the generated hydrogen bubbles to detach, and more bubbles cover the electrode surface, thereby affecting the performance of the catalyst. This phenomenon may lead to gas accumulation, thereby reducing the reaction efficiency. Therefore, in order to further optimize the performance of the catalyst, the idea of enhancing the hydrophilicity of the catalyst is selected. The present invention adds hydrophilic carbon black powder to the reaction solution of the synthetic catalyst to enhance the hydrophilicity of the catalyst. The experimental results show that the addition of this hydrophilic material can improve the surface properties of the catalyst, making it easier for the generated hydrogen bubbles to detach, thereby reducing the gas accumulation phenomenon and improving the reaction efficiency.
[0049] In summary, the present invention is synthesized by a simple one-step solvothermal method, and the same amount of acetylacetonate platinum (C 10 H 14 O 4 Pt), acetylacetonate palladium (C 10 H 16 O 4 Pd), cobalt acetylacetonate (C 10 H 16 CoO 4 ), nickel acetylacetonate (C 10 H 14 NiO 4 ) and copper acetylacetonate (C 10 H 14 CuO 4 ) and add a certain amount of carbon material to synthesize a powdered catalyst, which is then prepared into catalyst ink, drop-coated on a glassy carbon electrode, dried in air, and then used in electrochemical reactions.
[0050] The PtPdCoNiCu-CB high entropy alloy catalyst prepared by the present invention has enhanced hydrophilicity compared to the PtPdCoNiCu high entropy alloy catalyst. The improved hydrophilicity affects the bubbles on the electrode surface during the electrolysis process, thereby improving the reaction activity of the catalyst and improving the catalytic performance under high current conditions. In addition, the enhanced hydrophilicity also makes the catalyst more stable during operation.
[0051] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a high entropy alloy water electrolysis hydrogen production catalyst modified by a hydrophilic carbon-based material, characterized in that: The following steps are involved: 1) adding the hydrophilic carbon-based material and the mixed metal salt into the ethylene glycol solution, and uniformly mixing them by ultrasonication to obtain a reaction solution; 2) The reaction solution obtained in step 1) is heated in an oil bath at 200-240° C. for 0.5-2 h, cooled and centrifuged to obtain a hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst.
2. The method for preparing a high entropy alloy catalyst for electrolyzing water to produce hydrogen using a carbon-based material modified according to claim 1, characterized in that: The hydrophilic carbon-based material is selected from hydrophilic carbon black, hydrophilic carbon cloth or hydrophilic biochar material.
3. The method for preparing a high entropy alloy water electrolysis hydrogen production catalyst modified by a hydrophilic carbon-based material according to claim 1, characterized in that: The purity of the ethylene glycol solution is 99.7% (GC).
4. The method for preparing a high entropy alloy water electrolysis hydrogen production catalyst modified by a hydrophilic carbon-based material according to claim 1, characterized in that: The mixed metal salt is prepared from platinum salt, palladium salt, cobalt salt, nickel salt and copper salt.
5. The method for preparing a high entropy alloy water electrolysis hydrogen production catalyst modified by a hydrophilic carbon-based material according to claim 4, characterized in that: The mixed metal salt is prepared from acetylacetonate platinum, acetylacetonate palladium, acetylacetonate cobalt, acetylacetonate nickel and acetylacetonate copper of the same molar mass.
6. The method for preparing a high entropy alloy water electrolysis hydrogen production catalyst modified by a hydrophilic carbon-based material according to claim 1, characterized in that: In step 1), the usage ratio of the carbon-based material and the mixed metal salt is (0.3-0.4) mg: (0.1-0.2) mmol.
7. The method for producing hydrogen from water electrolysis by modifying a high entropy alloy with a hydrophilic carbon-based material according to claim 1, characterized in that: In step 1), the ultrasonic mixing time is 0.25-0.75 h.
8. The method for producing hydrogen from water electrolysis by modifying a high entropy alloy catalyst using a hydrophilic carbon-based material according to claim 1, wherein: In step 2), the reaction solution was 230-260 μLs -1 Slowly add it dropwise into the ethylene glycol solution heated in an oil bath at a rate of 9. A hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst prepared by the method described in any one of claims 1 to 8, characterized in that: The hydrophilicity of the high entropy alloy water electrolysis hydrogen production catalyst modified by the hydrophilic carbon-based material is enhanced.
10. Use of the hydrophilic carbon-based material modified high entropy alloy water electrolysis hydrogen production catalyst according to claim 9 in water electrolysis hydrogen production reaction.
Citation Information
Patent Citations
Preparation method and application of CoS nanowire catalyst with surface doped and modified with MoS2
CN112439430A
High-entropy alloy nano powder with high specific surface area and preparation method thereof
CN115533111A
Preparation method of platinum electrode with high catalytic hydrogen evolution activity
CN115896805A
Preparation method of high-entropy alloy catalyst, high-entropy alloy catalyst and application
CN116799229A
High-entropy alloy nano-particles, catalyst and application of high-entropy alloy nano-particles and catalyst
CN117943535A
Cited By
High-entropy intermetallic compound bifunctional catalyst as well as preparation method and application thereof
CN120280508A
High-entropy intermetallic compound bifunctional catalyst and preparation method and application thereof
CN120280508B